Microbial carbon use efficiency along an altitudinal gradient - Mganga, Kevin Z.; Sietiö, Outi-Maaria; Meyer, Nele; Poeplau, Christopher; Adamczyk, Sylwia; Biasi, Christina; Kalu, Subin; Räsänen, Matti; Ambus, Per; Fritze, Hannu; Pellikka, Petri K.E.; Karhu, Kristiina (Soil biology & biochemistry, 2022)
Soil microbial carbon-use efficiency (CUE), described as the ratio of growth over total carbon (C) uptake, i.e. the sum of growth and respiration, is a key variable in all soil organic matter (SOM) models and critical to ecosystem C cycling. However, there is still a lack of consensus on microbial CUE when estimated using different methods. Furthermore, the significance of many fundamental drivers of CUE remains largely unknown and inconclusive, especially for tropical ecosystems. For these reasons, we determined CUE and microbial indicators of soil nutrient availability in seven tropical forest soils along an altitudinal gradient (circa 900–2200 m a.s.l) occurring at Taita Hills, Kenya. We used this gradient to study the soil nutrient (N and P) availability and its relation to microbial CUE estimates. For assessing the soil nutrient availability, we determined both the soil bulk stoichiometric nutrient ratios (soil C:N, C:P and N:P), as well as SOM degradation related enzyme activities. We estimated soil microbial CUE using two methods: substrate independent 18O-water tracing and 13C-glucose tracing method. Based on these two approaches, we estimated the microbial uptake efficiency of added glucose versus native SOM, with the latter defined by 18O-water tracing method. Based on the bulk soil C:N stoichiometry, the studied soils did not reveal N limitation. However, soil bulk P limitation increased slightly with elevation. Additionally, based on extracellular enzyme activities, the SOM nutrient availability decreased with elevation. The 13C-CUE did not change with altitude indicating that glucose was efficiently taken up and used by the microbes. On the other hand, 18O-CUE, which reflects the growth efficiency of microbes growing on native SOM, clearly declined with increasing altitude and was associated with SOM nutrient availability indicators. Based on our results, microbes at higher elevations invested more energy to scavenge for nutrients and energy from complex SOM whereas at lower elevations the soil nutrients may have been more readily available. •We studied soil nutrient availability in Kenyan tropical mountain forests.•We estimated also microbial carbon-use efficiency (CUE) along the gradient.•We assume that different in situ soil temperatures are seen as legacy effect in CUE.•Bulk stoichiometric C:nutrient ratios did not indicate nutrient limitation.•Enzyme activities and CUE showed greater need to decompose SOM in higher elevations.